1997
DOI: 10.1063/1.52847
|View full text |Cite
|
Sign up to set email alerts
|

The “Micromorph” cell: a new way to high-efficiency-low-temperature crystalline silicon thin-film cell manufacturing?

Abstract: Abstract. Hydrogenated microcrystalline Silicon (µc-Si:H) produced by the VHF-GD (Very High Frequency Glow Discharge) process can be considered to be a new base material for thin-film crystalline silicon solar cells. The most striking feature of such cells, in contrast to conventional amorphous silicon technology, is their stability under lightsoaking. With respect to crystalline silicon technology, their most striking advantage is their low process temperature (220°C). The so called "micromorph" cell contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…First concept was a-Si/a-SiGe but, as the cost of the Ge precursors is high and the electronic quality of the a-SiGe:H layers is lower than for a-Si:H layers, a lot of effort is being done in replacing the a-SiGe:H part of the cell by other solutions like microcrystalline Si [6]. This leads to the 'micromorph' cell concept combining an a-Si:H top cell with a microcrystalline Si bottom cell [1] as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…First concept was a-Si/a-SiGe but, as the cost of the Ge precursors is high and the electronic quality of the a-SiGe:H layers is lower than for a-Si:H layers, a lot of effort is being done in replacing the a-SiGe:H part of the cell by other solutions like microcrystalline Si [6]. This leads to the 'micromorph' cell concept combining an a-Si:H top cell with a microcrystalline Si bottom cell [1] as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenated amorphous (a-Si:H) and microcrystalline ( c-Si:H) silicon are well suited for combination in a tandem solar cell [1][2][3]. An essential requirement for high efficiency is a good current matching as the cell with lower current limits the whole device.…”
Section: Introductionmentioning
confidence: 99%
“…The case of the 7.5% is more complicated. In this series, σ dark is strongly influenced by the oxygen content which varies from 3x10 19 (20 W sample) to 7x10 18 cm -3 (70 W sample). At these very high level of oxygen contamination, it is quite surprising that corresponding cells incorporating the same i-layer can still behave satisfactorily (see Fig.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…silane dilution and plasma power (or the resulting deposition rate). On the other hand, it has been shown that these structural parameters (preferential orientation and columnar structure) can be controlled, in specific cases (for example using an argon and hydrogen dilution of silane), by the deposition conditions [19]. [20,21].…”
Section: Structural Propertiesmentioning
confidence: 99%